DAMPAK PENERAPAN âSAK ETAPâ: STUDI KASUS PADA GROUP BANK PERKREDITAN RAKYAT - Andini, Bayu Nurcahyo (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to explain the impact of implementing of Financial Accounting Standards forEntities without Public Accountability (SAK ETAP) at Rural Bank (BPR) and to understand the opinion of thefinancial statementâs prepare and external auditor on the implementation of SAK ETAP at BPR so it can beconcluded whether SAK ETAP is the correct accounting standard for BPR. This research is a qualitativeresearch with case study approach at a group of BPR which consist of four BPR, which their shares are owned byone family. The data is collected through interviews, observations and documentations. Interviews are done withthe directors, head of operational, accounting departments, and external auditors. The result of research showsthat the implementation of SAK ETAP at BPR has an impact to the provision revenue, the deferred cost, theincome tax and the preparation and the presentation of BPR financial report. However, this impact has noinfluence overall on BPR financial report. The implementation of SAK ETAP at BPR creates lessimplementation cost than the benefit which is gained by BPR, and also SAK ETAP is the accounting standardfor BPR characteristics.Keywords: the impact of implementing, the appropriate financial accounting standards, SAK ETAP, Rural Bank